Dual roles of earthworms in climate change: Emission contributors or climate mitigators? - Syarifinnur (Journal of Critical Ecology, 2026)
Background:  Soil biodiversity is a key element of terrestrial ecosystems that underpins their resilience to environmental stress, especially amid accelerating climate change. Among soil organisms, earthworms are vital ecosystem engineers that regulate soil structure, nutrient cycling, and organic matter decomposition. However, intensive land use and climatic pressures have led to declining soil biodiversity, threatening ecosystem stability and sustainable land management. Methods: This review synthesizes recent empirical and experimental studies on the dual roles of earthworms in carbon and nitrogen cycling, soil organic carbon (SOC) accumulation, and greenhouse gas (GHG) fluxes under different management systems. Findings: The analysis emphasizes conservation tillage, organic amendments, and precision nutrient management as key strategies influencing earthworm-mediated processes. Evidence shows that earthworm activity can increase nitrous oxide (N₂O) emissions by up to 42% in nitrogen-enriched soils. Conversely, interactions with organic amendments such as compost and biochar can enhance SOC by up to 32.69%. Conservation tillage, particularly strip tillage, improves carbon sequestration (1.21 Mg C ha⁻¹ year⁻¹) and increases earthworm abundance by up to 133%. These results demonstrate that management practices strongly mediate the balance between earthworm-driven GHG emissions and carbon storage. Conclusion: Earthworms are central to sustainable agriculture through their roles in improving soil quality and mitigating climate impacts. Implementing earthworm-friendly practices, such as reduced tillage, organic matter addition, and balanced nutrient application, can optimize their ecological benefits while minimizing GHG emissions. Novelty/Originality of this article: This review provides an integrative perspective on the paradoxical function of earthworms as both GHG emitters and climate mitigators. It offers a conceptual framework to guide future research on enhancing carbon sequestration and sustainability through earthworm-based soil management.